Zastosowanie modeli opcyjnych w nowoczesnych ratingach wewnętrznych banku - Krysiak, Zbigniew (Application of the option model for internal rating systems in banks, 2006)
The above presented paper considers impact of selected micro and macro factors on probability of default (EDF) of the borrower. Estimated values of EDF, using option model, based on dates about companies drawn from Warsaw Stock Exchange were regressed to the selected factors. Dates were pooled out from period of five years from 1998 to 2002. Each separated factor was regressed to EDF. Based on that analysis in two tables were presented the results, which shows the correlation between EDF and specific factor. It seems that this research study proves that option model represents integrated tool for EDF analysis, because it reflects impact of several factors in one value. For father researches multidimensional regression analysis is advised. Based on the presented study, it seems that option model could be valuable tool for internal rating systems used by bank.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 224-234